REPELLENCY AND TOXICITY OF SOME BOTANICALS AGAINST SPODOPTERA LITURA FABRIUS ON GLYCINE MAX. LINN (SOYBEAN) - D. S. PATIL; N. S. CHAVAN (The Bioscan, 2010)
Bioefficacy of some botanicals was tested against Spodoptera litura, Fabrius on Glycine max. Linn. In present investigation Acorus calamus, Acacia concinna, Terminalia chebula, Terminalia belerica are selected for ethanolic extraction of their useful parts. Various dose levels were applied in the field of explore larvicidal potential of phytoextracts. Percentage mortality for various concentrations proved that Acacia concinna has effective potential with 85.2% mortality at 50 ppm dose level. Probit analysis gave median dose i.e. LC50, 25.37 ppm, which can be sustainable solution for ecofriendly management of Spodotera littura on Soybean (Glycine max.), using Acacia concinna pod extract.